Paradigma Positivisme dan Idealisme dalam Ilmu Sejarah: Tinjauan Reflektif Terhadap Posisi Sejarah Sebagai Ilmu - Arditya Prayogi (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2021)
Abstract This article is intended to describe the discourse related to the historical position that can be approached with a natural science approach and a social science approach. The natural science approach in the form of positivism philosophy influences the position of history as a science. Even so, the philosophical approach of idealism that is close to social science also has an influence on the historical position. This article uses a qualitative descriptive method with the library study method. From the results of the review, it is known that the positivism paradigm in historical studies makes history a science with an empirical-quantitative approach and makes humans and historical sources part of nature (inanimate objects). On the other hand, the idealism paradigm in historical studies makes history a unique unit. Keywords: Paradigm, Philosophy, Positivism, Idealism, History